Make-in-MCE:A Differentiating Alumni Initiative in an Engineering College - Krishnaswamy, S.; Mahendra, G.; Jayantha, K. S.; Amarendra, H. J.; Uma, B. (Journal of Engineering Education Transformations, 2017)
Alumni associations present first-hand opportunities for educational institutions to understand the ever-changing demands and expectations of the industry and to develop their curriculum accordingly. Alumni given their professional experience can identify such areas at the institute which need improvement and can make best efforts to provide the same to current students to experience better learning. The project based learning offers several advantages to students and significantly guides and helps in their career immediately after graduation. One major issue with student projects is in getting a good problem to work and an effective mentoring. Our alumni have made a sincere and big attempt to address this problem. This paper presents a case study of the recent venture by our alumni to help ambitious students to launch their own venture immediately after graduation.